2022
DOI: 10.20344/amp.13870
|View full text |Cite
|
Sign up to set email alerts
|

Inibidores da PARP: do mecanismo de ação à prática clínica

Abstract: Repairing damage and errors that occur in the DNA molecule is essential to maintain the integrity of the genome and cell viability. Deficits in DNA repair mechanisms lead to an increased risk of genetic instability and contribute to neoplastic transformation. Poly (ADP-ribose) polymerases (PARP) are a group of enzymes that play a key role in signalling and repairing DNA errors. The inhibition of its activity is a therapeutic strategy that takes advantage of the mechanism of synthetic lethality and that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Fibromyalgia syndrome is a widespread pain disorder thought to have altered central pain processing. 18 , 19 ) HNPP with whole-body pain may overlap the fibromyalgia criteria and potentially delay the diagnosis of HNPP. 8 )…”
Section: Discussionmentioning
confidence: 99%
“…Fibromyalgia syndrome is a widespread pain disorder thought to have altered central pain processing. 18 , 19 ) HNPP with whole-body pain may overlap the fibromyalgia criteria and potentially delay the diagnosis of HNPP. 8 )…”
Section: Discussionmentioning
confidence: 99%
“…According to Sherin et al, in silico studies have demonstrated that ETV could potentially be a candidate for breast, ovarian, and prostate cancer treatment, because it could inhibit the enzyme PARP1 that is expressed in these tissues, which plays a crucial role in DNA signaling and DNA damage repair [12]. Therefore, by inhibiting PARP in cancer cells, there would be the accumulation of unrepaired errors that ultimately lead to cell death [12,13].…”
Section: Parp Inhibitormentioning
confidence: 99%
“…Proteins such as BRCA1, BRCA2, PALB2, ATM, CHEK1, CHEK2, and RAD51 are involved in the HR repair process, while poly(ADP-ribose) polymerases 1 and 2, referred to as PARP1 and PARP2, are associated with the BER, with some of these proteins being frequently mutated in cancer patients. PARP not only act as regulators of the identification and repair process for SSB through BER, but also play a role in repairing DSB because they promote the activation of the repair by HR while inhibiting less conservative repair pathways such as the non-homologous route end joining (NHEJ) [13,14].…”
Section: Parp Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Deleterious alterations in genes involved in homologous recombination repair (HRR) are usually associated with an aggressive phenotype of PC but might also convey sensitivity to treatment with polyadenosine diphosphate-ribose (PARP) inhibitors (PARPi) through a mechanism of “synthetic lethality”, a phenomenon which occurs when the combination of two genetic events results in cell death, whereas a deficiency of only one of these genes does not [ 25 ]. PARPi are molecules targeting a specific DNA damage repair system, leading tumoral cells to irreparable injury and subsequent death [ 26 , 27 , 28 ]. In PC, olaparib is approved by the European Medicines Agency (EMA) in patients with mCRPC and BRCA 1/2 mutations (germline and/or somatic) who have progressed following prior therapy, including ARPI [ 29 ].…”
Section: Introductionmentioning
confidence: 99%